PERANCANGAN WEBSITE SEBAGAI PENDUKUNG SISTEM INFORMASI PEMASARAN PADA PT. ARMADA FINANCE JAMBI - Elzas - (JURNAL AKADEMIKA)
PT. ARMADA FINANCE everlastingly gets commitment to give the best one contribution for nation and state. PT's opportunity. Finance's fleet in expand its effort in harmony with it longterm commitment in pets environmentally, good relationship with society, consumer, effort friend, stockholder, government and keberlanjutan is PT's effort activity. Finance's fleet. PT. Finance's fleet realises that with see its effort of various perspective, multiple diverse behalf its behalf functionary can materialize harmonious ala. Whole Conduit and PT's Employee. Fleet Finance will work as to establish point and trips its life ala harmoniousing to give optimal contribution with aim most composes it the better life at proximately. To the effect of observational it is design one information system gets website's basis that cans be tool help to divide PT.ARMADA FINANCE to give information to society in term marketing. This information system application is designed by use of language pemograman PHP with database utilizes PHPMysql.